A taxa de desenvolvimento de força durante contrações isocinéticas dos extensores do joelho não é afetada pelo alongamento estático em indivíduos ativos - Souza, Renata Helena (2015)
Abstract The objective of this study was to investigate the influence of active static stretch (SS) on the peak torque (PT) and rate of force development (RFD) of knee extensors. Twelve active subjects performed the following tests in random order: 1) Five maximal isokinetic concentric contractions for knee extensors at 60 and 180°.s−1 to determine PT and RFD, and; 2) The same protocol after two SS exercises for the dominant leg extensors (10 × 30 s for each exercise). There was no modification of PT and RFD after the SS for both velocities. The time corresponding to the delta of initial angles of movement (90-80°) at 180°.s−1 was significantly reduced after SS. It is possible to conclude that SS exercises may increase the velocity of movement during explosive actions, without modifing the PT and RFD.